Sobre a possibilidade de pensarmos o mundo: o debate entre John McDowell e Donald Davidson - Marco Aurelio Sousa Alves (2008)
This thesis evaluates a contemporary debate concerning the very possibility of thinking about the world. In the first chapter, McDowell's critique of Davidson is presented, focusing on the coherentism defended by the latter. The critique of the myth of the given (as it appears inSellars and Wittgenstein), as well as the necessity of a minimal empiricism (which McDowell finds in Quine and Kant), lead to an oscillation in contemporary thinking between two equally unsatisfactory ways of understanding the empirical content of thought. In the second chapter, I defend Davidson's approach, focusing on his theory of interpretation and semantic externalism, as well as on the relation between causes and reasons. In the third chapter, the debate is analyzed in more detail. I criticize the anomalous monism, the way in which the boundaries between the conceptual and the non-conceptual are understood by Davidson, as well as the naturalized Platonism defended by McDowell. This thesis is mainly negative, and it concludes by revealing problems in both positions under evaluation.